Farming Systems: Future Challenges for the Use of Draught Animals in Agricultural Development with Emphasis on Sub-Saharan Africa - Jones, Jim Ellis; Neill, Dave O; Riches, Charlie; Sims, Brian (Annals of Arid Zone, 2016)
Sub-Saharan Africa (SSA) has the tragic distinction of being the only region in the world where overall food security and livelihoods are deteriorating. It is becoming increasingly realized that poverty reduction can be constructively addressed by boosting smallholder agriculture. Livestock can play a critical role in improving the livelihoods of rural people engaged in smallholder agriculture, generating cash income from sales and making a wider input to crop production through provision of both draught and manure. Draught animals have a long and successful history in agricultural production playing a key role in meeting the power requirements of different farming systems in many parts of the world. With most rural households in SSA being dependent on human power for their tillage operations, returns to labor are very low, requiring arduous, back-breaking work. Furthermore, HIY/AIDS is reducing labor productivity. There is clear potential for increasing the use of draught animal power (DAP) in the region to alleviate increasing labor shortages for both agricultural production and local transport. While DAP can be sustainable, affordable and appropriate, requiring few external inputs, there are many challenges associated with its use. Improving the productivity of DAP can be realized through increasing its availability, using existing animals more effectively, improving animal health and their ability to work or reducing the demand for DAP. This can be achieved through improved availability, better maintenance and use of implements, in particular animal-drawn weeders, or reduced tillage and conservation agriculture systems. DAP technologies are appropriate and affordable, but their improvement requires an integrated and participatory approach to ensure that labor productivity is improved, food security is enhanced and household incomes are increased.